Combined simulation and ex vivo assessment of free-edge length in bicuspidization repair for congenital aortic valve diseaseCentral MessagePerspective - Perry S. Choi, MD; Amit Sharir, BS; Yoshikazu Ono, MD; Masafumi Shibata, MD; Alexander D. Kaiser, PhD; Yellappa Palagani, PhD; Alison L. Marsden, PhD; Michael R. Ma, MD (JTCVS Open)
Objective: The study objective was to investigate the effect of free-edge length on valve performance in bicuspidization repair of congenitally diseased aortic valves. Methods: In addition to a constructed unicuspid aortic valve disease model, 3 representative groups—free-edge length to aortic diameter ratio 1.2, 1.57, and 1.8—were replicated in explanted porcine aortic roots (n = 3) by adjusting native free-edge length with bovine pericardium. Each group was run on a validated ex vivo univentricular system under physiological parameters for 20 cycles. All groups were tested within the same aortic root to minimize inter-root differences. Outcomes included transvalvular gradient, regurgitation fraction, and orifice area. Linear mixed effects model and pairwise comparisons were used to compare outcomes across groups. Results: The diseased control group had a mean transvalvular gradient of 28.3 ± 5.5 mm Hg, regurgitation fraction of 29.6% ± 8.0%, and orifice area of 1.03 ± 0.15 cm2. In ex vivo analysis, all repair groups had improved regurgitation and transvalvular gradient compared with the diseased control group (P < .001). Free-edge length to aortic diameter of 1.8 had the highest amount of regurgitation among the repair groups (P < .001) and 1.57 the least (P < .001). Free-edge length to aortic diameter of 1.57 also exhibited the lowest mean gradient (P < .001) and the largest orifice area (P < .001). Conclusions: Free-edge length to aortic diameter ratio significantly impacts valve function in bicuspidization repair of congenitally diseased aortic valves. As the ratio departs from 1.57 in either direction, effective orifice area decreases and both transvalvular gradient and regurgitation fraction increase.